2008
DOI: 10.2337/dc08-1242
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival of Diabetic Foot Ulcer Patients 1995–2008

Abstract: OBJECTIVE -The purpose of this study was to determine whether a strategy of aggressive cardiovascular risk management reduced the mortality associated with diabetic foot ulceration. RESEARCH DESIGN AND METHODS-After an initial audit of outcomes demonstrating a high mortality rate in 404 diabetic foot ulcer patients with the first ulceration developing between 1995 and 1999, a new aggressive cardiovascular risk policy was introduced as standard practice at the Diabetic Foot Clinic, Royal Infirmary of Edinburgh,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 26 publications
5
93
0
3
Order By: Relevance
“…91 In Helsinski, Finland, the emphasis on active vascular intervention has resulted in a decrease in the incidence of major amputation both in nondiabetic and in diabetic patients, 92 and in Scotland, Matthew Young at the Edinburgh Diabetic Foot Clinic reported a decrease in mortality of diabetic foot patients after aggressive treatment of vascular risk factors. 93 Research has been a prominent feature of many diabetic foot clinics, with work presented at national and international meetings as well as at diabetic foot meetings, such as the Diabetic Foot Study Group, and the biennial Malvern Diabetic Foot meeting. William Jeffcoate and Fran Game set up a Foot Ulcer Trials Unit in Nottingham in 2002, and recently reported the outcomes of two studies coordinated from that center.…”
Section: System Changes Research and Reduction In Amputation Ratesmentioning
confidence: 99%
“…91 In Helsinski, Finland, the emphasis on active vascular intervention has resulted in a decrease in the incidence of major amputation both in nondiabetic and in diabetic patients, 92 and in Scotland, Matthew Young at the Edinburgh Diabetic Foot Clinic reported a decrease in mortality of diabetic foot patients after aggressive treatment of vascular risk factors. 93 Research has been a prominent feature of many diabetic foot clinics, with work presented at national and international meetings as well as at diabetic foot meetings, such as the Diabetic Foot Study Group, and the biennial Malvern Diabetic Foot meeting. William Jeffcoate and Fran Game set up a Foot Ulcer Trials Unit in Nottingham in 2002, and recently reported the outcomes of two studies coordinated from that center.…”
Section: System Changes Research and Reduction In Amputation Ratesmentioning
confidence: 99%
“…8 For those who experience diabetes-related amputations, the 5-year survival is poor, with mortality estimates of between 25% and 50% in 1985 in UK populations. 9,10 Changes in diabetes-related LEAs have been reported in parts of the UK. In common with some European countries and the USA, major LEA rates in Scotland have been reported to fall.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…However, it would seem appropriate that these patients should be initially assessed in a similar manner to the patient with a non-ulcerated (intact) foot. Identification of the patient with PAD is essential to optimise management of the foot ulcer and in undertaking other measures to mitigate cardiovascular risk [20]. Patients should be informed that they have PAD and that it confers an increased risk to their foot.…”
Section: Rationalementioning
confidence: 99%
“…antiplatelet agent, statin and antihypertensive medication when indicated) reduced 5-year mortality from 58% to 36% [20].…”
Section: Rationalementioning
confidence: 99%